Identification of the Plasmid-Mediated Colistin Resistance Gene mcr-1 in Escherichia coli Isolates From Migratory Birds in Guangdong, China - Zhang, Yan; Kuang, Xu; Liu, Juan; Sun, Ruan-Yang; Li, Xing-Ping; Sun, Jian; Liao, Xiao-Ping; Liu, Ya-Hong; Yu, Yang (Frontiers in Microbiology, 2021)
We determined the prevalence and transmission characteristics of mcr-1-positive Escherichia coli (MCRPEC) isolates from migratory birds Anser indicus in Guangdong, China. We identified 22 MCRPEC from 303 A. indicus fecal samples (7.3%) in Guangzhou, Zhaoqing, and Futian. The mcr-1 gene coexisted with 24 other types of antibiotic resistance genes (ARG), and 11 ARGs were highly prevalent at levels >50%. The MCRPEC displayed a diversity of sequence types (ST), and 19 distinct STs were identified with ST10, ST1146, and ST1147 as the most prevalent. In addition, these MCRPEC from birds were closely related phylogenetically to those from other sources in China. Whole-genome sequencing analysis demonstrated that mcr-1 was located on IncX4 (n=9, 40.9%), IncI2 (n=5, 22.7%) and IncP (n=1, 4.5%) plasmids and the latter shared an identical plasmid backbone with other sources. These results highlight the significance of migratory birds in the transmission of antibiotic resistance and provide powerful evidence that migratory birds are potential transmitters of antibiotic resistance.